Penambahan Sari Lengkuas Merah (Alpinia purpurata) Dalam Edible Coating Pati Sagu Meranti Terhadap Sifat Kimia, Mikrobiologi dan Kesukaan Buah Tomat (Lycopersicum esculentum Mill) - Dewi Fortuna Ayu; Raswen Efendi; Vonny Setiaries Johan; Lutfi Habibah (Agricultural Faculty, 2020)
This research aim was to study the application of red galanga juice addition in meranti sago starch edible coating on chemical, microbiology, and hedonic properties of tomatoes during storage. The study used a Completely Randomized Design (CRD) with 5 treatments and 3 replications so that 15 (fifteen) experimental units were obtained. The treatments used were P0 (without addition of red galangal juice), P1 (1% addition of red galangal juice), P2 (3% addition of red galangal juice), P3 (5% addition of red galangal juice), and P4 (7 % addition of red galangal juice) in formulation of sago starch edible coating which applicated on tomatoes during 21 days storage. The data obtained were statistically analyzed using Anova and DNMRT at a 5% level. The results showed that the addition of red galangal juice significantly affected weight loss, total dissolved solids, hardness, total microbes, and hedonic organoleptic assessment of the tomato texture. The addition of red galangal juice in edible coating didn’t significantly affect the organoleptic assessment of the tomato color. The best treatment of this research was P4 which showed on tomatoes after 21 days storage that had 16.38% weight loss, 1.39 °Brix total dissolved solids, 5.83 kg/f hardness, 5.52 log CFU/g total microbes, and overall hedonic assessment of color was 2,70 (somewhat like), and 3.26 texture (somewhat like).